Community-based models of care facilitating the recovery of people living with persistent and complex mental health needs: a systematic review and narrative synthesis - Harvey, Carol; Zirnsak, Tessa-May; Brasier, Catherine; Ennals, Priscilla; Fletcher, Justine; Hamilton, Bridget; Killaspy, Helen; McKenzie, Peter; Kennedy, Hamilton; Brophy, Lisa (Frontiers in Psychiatry, 2023)
To assess the effectiveness of community-based models of care (MoCs) supporting the recovery of individuals who experience persistent and complex mental health needs.We conducted a systematic review and narrative synthesis of MoC studies reporting clinical, functional or personal recovery from October 2016-October 2021. Sources were Medline, EMBASE, PsycInfo, CINAHL and Cochrane databases. Studies were grouped according to MoC features. The narrative synthesis was led by our researchers with lived experience.Beneficial MoCs ranged from well-established to novel and updated models, and those explicitly addressing recovery goals and incorporating peer support: Goal Focused; Integrated Community